Penerapan Surgical Safety pada Penata Anestesi Melalui Media Video Edukasi - Fransi Arsani; Prayitno Prayitno; Nabhani Nabhani (Lembaga Pengembangan Kinerja Dosen, 2024)
Patient safety in surgical procedures is a critical element that must be addressed by medical professionals, including anesthesiologists. The World Health Organization's (WHO) Surgical Safety Checklist (SSC) is designed to enhance patient safety during surgery, but its implementation still encounters several challenges, such as insufficient training and limited resources. This study aims to improve anesthesiologists’ understanding and compliance with the SSC through the use of educational video media. The research methods involved socialization, video-based training, hands-on practice, and evaluation with a participatory approach. The participants were anesthesiologists who received a structured training session using videos that explained the SSC steps and emphasized its importance. Pre- and post-training assessments were conducted to measure changes in understanding and compliance.The results demonstrated a significant improvement in both the anesthesiologists’ understanding and compliance with the SSC after the training. The average understanding score increased from 60.5 to 85.3, while compliance rose from 55.2 to 88.7. These findings indicate that educational videos are an effective tool for enhancing anesthesia service quality and increasing medical personnel’s access to training. The study emphasizes the importance of technology-based education to overcome barriers related to limited resources and training opportunities. Based on these results, the study recommends the implementation of similar video-based educational methods in training programs for other medical personnel, aiming to improve patient safety across various healthcare settings.